Synthesis, Characterization and In Vitro and In Silico Biological Evaluation of New Mannich-Based Rhodanine and Thiazolidine-2,4-dione Derivatives as Potential Anti-Lung-Cancer Agents - Ateşoğlu, Şeyma; Çakır, Furkan; Şenol, Ayşe Merve; Tokalı, Pelin; Şenol, Halil; Tokalı, Feyzi Sinan; Akbaş, Fahri; Kalay, Erbay (Synlett, 2025)
In this study, 10 new rhodanine and thiazolidine-2,4-dione derivatives based on Mannich-modified vanillin were synthesized, characterized, and evaluated for their anticancer potential against A549 lung cancer and BEAS-2B normal cells. Among them, compound 5c exhibited the most potent anticancer activity, with an IC50 of 2.43 μM and a selectivity index of 10.91, showing higher selectivity than the reference drug sorafenib. Molecular docking studies suggested 5c as a strong potential epidermal growth factor receptor (EGFR) inhibitor, supported by a docking score of –9.827 kcal/mol and key interactions with residues such as Met-793, Leu-788, and Phe-856. Molecular dynamics simulations further confirmed the stability of the 5c-EGFR complex. ADMET predictions indicated favorable pharmacokinetic and safety profiles for 5c, including high permeability, oral absorption, and no significant toxicity. These findings highlight 5c as a promising lead compound for targeted lung cancer therapy, warranting further preclinical studies.
Keywords: Mannich base; rhodanine; thiazolidine-2,4-dione; molecular docking; A549